Altered expression of chondroitin sulfate structure modifying sulfotransferases in the articular cartilage from adult osteoarthritis and Kashin-Beck disease. Issue 8 (August 2017) - Han, J.; Li, D.; Qu, C.; Wang, D.; Wang, L.; Guo, X.; Lammi, M.J.
Summary: Objective: To investigate the expression of enzymes involved in chondroitin sulfate (CS) sulfation in the articular cartilage isolated from adult patients with osteoarthritis (OA) and Kashin-Beck disease (KBD), using normal adults as controls. Methods: Articular cartilage samples were collected from normal, OA and KBD adults aged 38–60 years old, and divided into three groups with six individual subjects in each group. The morphology and pathology grading of knee joint cartilage was examined by Safranin O staining. The localization and expression of enzymes involved in CS sulfation (CHST-3, CHST-11, CHST-12, CHST-13, carbohydrate (N-acetylgalactosamine 4-sulfate 6-O) sulfotransferase 15 – CHST-15, and uronyl 2-O-sulfotransferase – UST) were examined by immunohistochemical (IHC) staining and semi-quantitative analysis. Results: Positive staining rates for anabolic enzymes CHST-3, CHST-12, CHST-15, and UST were lower in the KBD and OA groups than those in the control group. Meanwhile, reduced levels of CHST-11, and CHST-13 in KBD group were observed, in contrast to those in OA and control groups. The expressions of all six CS sulfation enzymes were less detected in the superficial and deep zones of KBD cartilage compared with control and OA cartilage. Conclusion: The reduced expression of the CS structure modifying sulfotransferases in the chondrocytes of both KBD and OA adult patients may provide explanations for their cartilage damages, and therapeutic targets for their treatment.